AN ANALYSIS OF THE PERSONALITY OF THE MAIN CHARACTER IN “THE DIARY OF A YOUNG GIRL” NOVEL - SYAHRUL EFENDI LUBIS (LP2MTBM MAKARIOZ, 2020)
In this thesis, the researcher chose THE DIARY OF A YOUNG GIRL as her analysis. The researcher was interested topersonality the main character of this novel whose name is Anne Frank. The major objective of this study is to find thechange of the personality of the main character in the novel. The sample was selected from the lines in the novel which werethe main character‟s thought and activities. This research used the method of qualitative research. Qualitative research isone of the research procedure which produces descriptive data in the form of speech and written. On the basis of the resultof this research, it can be concluded that the personality of the main character in THE DIARY OF A YOUNG GIRL generallychanged from extraversion to neuroticism, though the researcher could still find some facets of extraversion when the maincharacter showed the dominant character of neuroticism.